Removal of COD, turbidity and color in domestic wastewater using batch and continuous electrocoagulation system - Pempeña, Claribelle L.
The present study investigated the application of electrocoagulation (EC) process in the treatment of the domestic wastewater using aluminum (Al) electrode as the sacrificial anode and stainless-steel (SS) a cathode in both batch and continuos-flow systems. Response Surface methodology (RSM) using central Composite Design (CCD) was utilized in the batch system to evaluate the optimum operating conditions that were current density = 83.63 A/m², electrode distance = 8mm, treatment time = 31.92 min and pH=7.39 on COD, turbidity and color removal efficiency of 66.11%, 94.44% and 93.48% respectively. The dissolution rate of Al anode is dependent on pH and current density, therefore the removal efficiencies increased when the current density, pH along with the treatment time were also increased. However, removal efficiencies decreased when inter-electrode distance was increased because of an increase in cell resistance attributed to the decrease in the electrical conductivity of wastewater. In a continuous-flow system, the effects of current density and inlet flowrate were evaluated through time series and curve fitting. An increase in current density along with an increase in hydraulic retention time led to an increase in removal efficiency due to the formation rate of anodic dissolution of Al3+ ions causing coagulation. The optimum current density at constant flowrate for continuous-flow system was 30 A/m² resulted to high removal efficiency values of 80.92% for COD, 93.24% for turbidity and 92.16% for color. While the slowest flowrate was the optimum inlet flowrate of 2.86 ml/min corresponded to highest removal efficiency of 79.50% for COD, 93.87 for turbidity and 93.27% for color. Therefore, this study proved that electrocoagulation process is an effective method of treatment of domestic wastewater using a batch and continuous-flow system.